The history of Koi aquaculture in Singapore from 1965 to the present : translating translocated scientific knowledge from Japan into biosecurity - Tan, Delfinn Sweimay (2018)
Koi is a non-native ornamental commercially valuable species imported and cultivated as an ornamental fish in Singapore. In this thesis, I analysed the translocation of Japanese koi to Singapore from 1965 to 2018. In order to successfully translocate koi from Japan to Singapore, its environment had to be translated into scientific and vernacular knowledge which were translated into Singapore farm practices, policies and regulations by different social groups. Singaporean hobbyists attribute many of the differences among the koi kept in Japan versus that of in Singapore to the difference in climate and environment, in particular different water conditions. My study was an attempt to answer these questions: First, how and why did ornamental aquaculture practices in Singapore change over time? Second, what did Singapore take from Japan's koi cultivation practices, and how did they change them? Finally, what kind of knowledge is derived from koi aquaculture? I answered these questions by analysing the kind of knowledge that emerged from the translocation of koi and the translation of this knowledge into Singapore farm practices, government policy and regulations. I conducted semi-structured interviews and participant observation, and used snowball sampling to obtain interviewees, between June 2015 to the end of 2016 in both Singapore and Niigata Prefecture, Japan. I used document sources to build a qualitative history of the ornamental aquaculture industry of Singapore. I analysed the kinds of knowledge generated by the people working within agriculture, prioritizing ornamental fish aquaculture. I used thematic analysis to code my data and obtain themes. Two main themes emerged: the importance of water and the biosecurity of koi aquaculture in Singapore from the analytic lenses translation and translocation.